A Novel STAT3 Gain-of-Function Mutation in Fatal Infancy-Onset Interstitial Lung Disease - Deng, Mengyue; Li, Yue; Li, Yulu; Mao, Xiaolan; Ke, Han; Liang, Weiling; Lei, Xiaoguang; Lau, Yu-Lung; Mao, Huawei (Frontiers in Immunology, 2022)
Signal transducer and activator of transcription 3 (STAT3) gain-of-function (GOF) mutations cause early-onset immune dysregulation syndrome, characterized by multi-organ autoimmunity and lymphoproliferation. Of them, interstitial lung disease (ILD) usually develops after the involvement of other organs, and the onset time is childhood and beyond rather than infancy. Here, we reported a patient who presented with fatal infancy-onset ILD, finally succumbing to death. Next-generation sequencing identified a novel heterozygous mutation in STAT3 (c.989C>G, p.P330R). Functional experiments revealed it was a gain-of-function mutation. Upon interleukin 6 stimulation, this mutation caused a much higher activation of STAT3 than the wild-type control. In addition, the mutation also activated STAT3 under the steady-state. The T helper 17 cell level in the patient was significantly higher than that in normal controls, which may contribute to the autoimmune pathology caused by the STAT3P330R mutation. Apart from Janus kinase (JAK) inhibitors, we also provided experimental evidence of a STAT3 selective inhibitor (stattic) effectively suppressing the activation of mutant STAT3 in vitro. Collectively, our study expanded the clinical spectrum of STAT3 GOF syndrome. STAT3 GOF mutation appears as a new etiology of ILD and should be considered in patients with early-onset ILDs. In addition to JAK inhibitors, the specific STAT3 inhibitor would be an appealing option for the targeted treatment.